Application of Social Network Analysis to Major Petrochemical Accident: Interorganizational Collaboration Perspective. (22nd October 2021) - Abbassinia, Marzieh; Kalatpour, Omid; Motamedzade, Majid; Soltanian, Alireza; Mohammadfam, Iraj
ABSTRACT: Objective: Crisis management in major accidents requires the collaboration among different organizations. One of the most important problems of crisis management is the lack of coordination between executive organizations. The aim of this study was to examine the structural characters and problems of interorganizational network during crisis in the petrochemical industry and provide solutions to achieve the highest performance in crisis management. Methods: The organizations involved in crisis management were identified through interviews and questionnaires. Gephi (0.9.1) software was used to examine interorganizational relationships. Results: In this study, the crisis management team consisted of 25 public and private organizations and non-governmental organizations. The highest betweenness centrality was observed in Crisis Management of Provincial Government (CMPG) (142.16) and Fire Department of Petrochemical Complex (FDC) (89.3). The highest closeness centrality was observed in FDC (0.77), CMPG (0.7), Shazand Governorate (0.7), and Crisis Management of University of Medical Sciences (0.7). Conclusions: Coordination between organizations plays an important role in crisis and emergency management, and social network analysis helps identify strengths and weaknesses of organizations involved in crisis management, overcome those weaknesses, and consequently achieve the best performance in crisis management.